CUSTOMS AND TRADITIONS RELATED TO MOURNING OF THE KARAKALPAKS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The mourning customs of the Karakalpaks living on the shores of the Aral Sea and their transformation are discussed in this article.